A brown tumor after biliopancreatic diversion for severe obesity. - Benhalima, K; Katrien, B; Mertens, A; Ann, M; Van den Bruel, A; Annick, V; Laga, K; Katrien, L; Vanderschueren, D; Dirk, V; Samson, I; Ignace, S; et al. (2009)
A case of a brown tumor due to iatrogenic malabsorption following biliopancreatic diversion (BPD) is presented. A 52 year old women with a history of BPD 2 years before was referred to orthopedic surgery because of a painful lytic lesion of the left ankle. A bone biopsy revealed a giant cell tumor compatible with the diagnosis of a brown tumor. Subsequent metabolic evaluation showed severe 25-hydroxy vitamin D deficiency and secondary hyperparathyroidism (PTH 60 ng/L or twice the upper normal limit). Bone mineral density was decreased at the femoral neck (0.50 g/cm(2) ; T score of -3.92 or 66% of the expected value) and lumbar spine (T score of -1.75 or 93% of the expected value). A brown tumor can be the presenting symptom of iatrogenic malabsorption due to BPD. This case illustrates the severity of potential bone complications after BPD and the necessity of lifelong surveillance and vitamin supplements after BPD.